Modelling compound flooding: a case study from Jakarta, Indonesia - William Bennett (Natural Hazards, 2023)
The paper investigates compound fooding from waves, sea surge and river fow in northern Jakarta, Indonesia, which is a global hotspot of fooding, by combining process-basedcoastal and river models. The coastal hydrodynamic modelling of Jakarta Bay in Indonesiashows that coastal storms can lead to a substantial increase in sea water level due to windand wave setup in the nearshore areas, including Muara Angke river inlet. The compoundfood hazard from a range of food scenarios was simulated and analysed. The results revealthat low-lying areas around the river inlet are prone to fooding even during regular, lowintensity storm events, while rarer storms caused extensive foods. Floods were not causedby direct overwashing of sea defences but by overspill of the banks of the river inlet due tohigh sea water level caused by wind set up, wave setup, and sea surge obstructing the drainage of the river and elevating its water level during storms. We also found that the sea levelrise combined with rapid land subsidence will inundate the existing coastal food defencesduring storms in future. The majority of the city will be below mean sea level by 2100. Theoverfow of existing coastal defences will lead to extensive fooding in northern, western,and eastern Jakarta unless the defences are upgraded to keep up with future sea level rise.